AI-powered live chatbots and smart tour guide apps in tourism: A literature review and future research directions - Ghasemi, Vahid; Yarahmadi, Parichehr; Kuhzady, Salar (Turyzm/Tourism, 2025)
This study explores the critical intersection in the tourism sector combining artificial intelligence (AI) technologies with conventional methods. This research outlines three main goals: assessing the use of AI chatbots in the tourism industry, reviewing existing literature on intelligent tour guide apps, and pinpointing areas for further research. It focuses on incorporating AI into the tourism industry, highlighting the effectiveness of tools such as ChatGPT. The systematic literature review examines the use of ChatGPT in pre-trip, en route, and post-trip scenarios, analyzing its effects on customer engagement. Using technology acceptance model (TAM) and unified theory of acceptance and use of technology (UTAUT) frameworks, the adoption of automated intelligent tour guides is explored. The research follows a systematic review methodology, adhering to PRISMA guidelines for methodological rigor and has uncovered several factors that impact the adoption of AI-based intelligent tour guides, offering valuable insights for academic scholars and industry experts.